Sex differences in the associations of physical activity and macronutrient intake with child body composition: A cross‐sectional study of 3‐ to 7‐year‐olds in Samoa. Issue 4 (10th January 2020) - Thompson, Avery A.; Duckham, Rachel L.; Desai, Mayur M.; Choy, Courtney C.; Sherar, Lauren B.; Naseri, Take; Soti‐Ulberg, Christina; Reupena, Muagatutia S.; Wetzel, Abigail I.; Hawley, Nicola L.
Summary: Background: Overweight/obesity is prevalent among children in the Pacific Islands, but its aetiology is poorly understood. Few studies have considered body composition in addition to body mass index–based measures. Objectives: To describe body composition among Samoan children and determine sex‐specific associations among dietary intake, physical activity, and body composition. Methods: Body composition (percent body fat [%BF], lean mass, and trunk‐to‐peripheral fat ratio) of n = 83 Samoan children (3‐7 y) was assessed using dual‐energy X‐ray absorptiometry. Children completed 7 days of objective physical activity monitoring. Mothers reported child nutritional intake using a 115‐item food frequency questionnaire. Stepwise generalized linear regression was used to determine independent associations of nutritional intake and physical activity with body composition. Results: Samoan children had higher average %BF than reported among other ethnic groups but lower trunk‐to‐peripheral fat ratios. In sex‐stratified analyses, quartile of carbohydrate intake was negatively associated with %BF ( β = −2.02 SE = 0.58; P < .001) in girls only. Among boys, physical activity (quartile of accelerometer counts per minute) was negatively associated with %BF ( β = −1.66 SE = 0.55; P < .01). Conclusions: Sex differences in the associations among nutritional intake, physical activity, and body composition may be important to consider as interventions are developed to address overweight/obesity among Samoan children.